Comparative larval growth rates of purebred African Catfish, Claria gariepinus and hybrid catfish, Clarias macrophalus (female) X Clarias gariepinus (male). - Gamuyao, Rico Ledesma
Catfish is considered as one of the world's most important fish in aquaculture. Among the most cultured species are Philippine catfish, Clarias macrocephalus and African catfish, Clarias gariepinus. C. macrocephalus has superior taste and meat quality. However, due to its slow growth and breeding activity, this species is rarely used in aquaculture. This led to the introduction of exotic and faster-growing species like the African catfish, C. gariepinus. Hybrids of C. macrocephalus and C. gariepinus are viable for aquaculture. Such hybrids are currently being cultured in Thailand and Malaysia because of the enhanced characteristics of both species - superior taste and meat quality and faster growth rates., A 4-week study was conducted to compare the growth rates of Clarias sp. larvae produced from the following crosses: C. gariepinus X X. gariepinus and C. macrocephalus ( ) X C. gariepinus ( ) and to determine which cross has the optimum growth rate. Results showed that the trend of specific growth rate (SGR) values of both purebred and hybrid crosses from weeks 1 to 4 decreasing. Continued feeding of the larvae on dry artificial diet (e.g. fry mash) results in poor fish growth. From weeks 1 to 4, the specific growth rate (SGR) of purebred C. gariepinus larvae is consistently higher than the hybrid C. macrocephalus ( ) X C. gariepinus ( ) larvae. However, using independent-samples t-test, the specific growth rate (SGR) for purebred cross (2.1467%) is significantly higher (P<0.05) compared to hybrid cross (1.8467%) only on week 3. From the linear regression equation, there was homogeneity of regression coefficients, or slopes, in the mean body lengths (MBLs) of hybrid C. macrocephalus ( ) X C. gariepinus ( ) and of purebred C. gariepinus larvae. This means that at early larval stage of hybrid C. macrocephalus ( ) X C. gariepinus ( ) and of purebred C. gariepinus, there was no significant difference in their growth rates.